Effects of bacterial and viral pathogen-associated molecular patterns (PAMPs) on multidrug resistance (MDR) transporters in brain endothelial cells of the developing human blood–brain barrier - Phetcharawan Lye; Enrrico Bloise; Stephen G. Matthews (Fluids and Barriers of the CNS, 2023)
Abstract Background The multidrug resistance (MDR) transporters, P-glycoprotein (P-gp, encoded by ABCB1) and breast cancer resistance protein (BCRP/ABCG2) contribute to the blood–brain barrier (BBB), protecting the brain from drug exposure. The impact of infection on MDR in the developing human BBB remains to be determined. We hypothesized that exposure to bacterial and viral pathogen-associated molecular patterns (PAMPs) modify MDR expression and activity in human fetal brain endothelial cells (hfBECs) isolated from early and mid-gestation brain microvessels. Methods We modelled infection (4 h and 24 h) using the bacterial PAMP, lipopolysaccharide (LPS; a toll-like receptor [TLR]-4 ligand) or the viral PAMPs, polyinosinic polycytidylic acid (Poly I:C; TLR-3 ligand) and single-stranded RNA (ssRNA; TLR-7/8 ligand). mRNA expression was assessed by qPCR, whereas protein expression was assessed by Western blot or immunofluorescence. P-gp and BCRP activity was evaluated by Calcein-AM and Chlorin-6 assays. Results TLRs-3,4 and 8 were expressed by the isolated hfBECs. Infection mimics induced specific pro-inflammatory responses as well as changes in P-gp/ABCB1 or BCRP/ABCG2 expression (P < 0.05). LPS and ssRNA significantly decreased P-gp activity at 4 and 24 h in early and mid-gestation (P < 0.03-P < 0.001), but significantly increased BCRP activity in hfBECs in a dose-dependent pattern (P < 0.05-P < 0.002). In contrast, Poly-IC significantly decreased P-gp activity after 4 h in early (P < 0.01) and mid gestation (P < 0.04), but not 24 h, and had no overall effect on BCRP activity, though BCRP activity was increased with the highest dose at 24 h in mid-gestation (P < 0.05). Conclusions Infectious PAMPs significantly modify the expression and function of MDR transporters in hfBECs, though effects are PAMP-, time- and dose-specific. In conclusion, bacterial and viral infections during pregnancy likely have profound effects on exposure of the fetal brain to physiological and pharmacological substrates of P-gp and BCRP, potentially leading to altered trajectories of fetal brain development.